Eco2 Cities : Ecological Cities as Economic Cities - Suzuki, Hiroaki (World Bank, 2012)
This book provides an overview of the World Bank's Eco2 cities : ecological cities as economic cities initiative. The objective of the Eco2 cities initiative is to help cities in developing countries achieve a greater degree of ecological and economic sustainability. The book is divided into three parts. Part one describes the Eco2 cities initiative framework. It describes the approach, beginning with the background and rationale. Key challenges are described, and lessons are drawn from cities that have managed to turn these challenges into opportunities. A set of four key principles is introduced. These principles are the foundation upon which the initiative is built. They are: (1) a city-based approach enabling local governments to lead a development process that takes into account their specific circumstances, including their local ecology; (2) an expanded platform for collaborative design and decision making that accomplishes sustained synergy by coordinating and aligning the actions of key stakeholders; (3) a one-system approach that enables cities to realize the benefits of integration by planning, designing, and managing the whole urban system; and (4) an investment framework that values sustainability and resiliency by incorporating and accounting for life-cycle analysis, the value of all capital assets, and a broader scope for risk assessment in decision making. Part two presents a city-based decision support system that introduces core methods and tools to help cities as they work toward applying some of the core elements and stepping stones. Part two looks into methods for collaborative design and decision making and methods to create an effective long-term framework able to help align policies and the actions of stakeholders. Part three consists of the Field Reference Guide. The guide contains background literature designed to support cities in developing more in-depth insight and fluency with the issues at two levels. It provides a city-by-city and sector-by-sector lens on urban infrastructure. The next section comprises a series of sector notes, each of which explores sector-specific issues in urban development.